Global evaluation of lineage-specific human papillomavirus capsid antigenicity using antibodies elicited by natural infection - Gathoni Kamuyu; Filomeno Coelho da Silva; Vanessa Tenet; John Schussler; Anna Godi; Rolando Herrero; Carolina Porras; Lisa Mirabello; John T. Schiller; Mónica S. Sierra; Aimée R. Kreimer; Gary M. Clifford; et al. (Nature Communications, 2024)
Abstract Human Papillomavirus (HPV) type variants have been classified into lineages and sublineages based upon their whole genome sequence. Here we have examined the specificity of antibodies generated following natural infection with lineage variants of oncogenic types (HPV16, 18, 31, 33, 45, 52 and 58) by testing serum samples assembled from existing archives from women residing in Africa, The Americas, Asia or Europe against representative lineage-specific pseudoviruses for each genotype. We have subjected the resulting neutralizing antibody data to antigenic clustering methods and created relational antigenic profiles for each genotype to inform the delineation of lineage-specific serotypes. For most genotypes, there was evidence of differential recognition of lineage-specific antigens and in some cases of a sufficient magnitude to suggest that some lineages should be considered antigenically distinct within their respective genotypes. These data provide compelling evidence for a degree of lineage specificity within the humoral immune response following natural infection with oncogenic HPV.